Педагогічні інновації у формуванні національної гуманітарно-технічної еліти - Романовський, Олександр Георгійович (НТУ "ХПІ", 2010)
The article is devoted to a problem of formation of national humanitarian-technical elite as strategic task of a higher school. It is determined and the list pedagogical innovation is proved which will assist efficiency of formation of national humanitarian-technical elite.
Keywords: педагогічні інновації; еліта; елітарність; лідер; педагогічна майстерність